Implementation Of Religious Moderation And Its Elevation To Religious Harmony In The Raren Batuah Community - Rahman, Anita; Ulfah, Aulia; Hindayani , Leni (Sharia Journal and Education Center Publishing, 2024)
Abstract This journal discusses the implementation of religious moderation and its relevance to religious harmony in the Raren community. The aim of this research is to identify and analyze the role of religious moderation in promoting inter-religious harmony in society. The research method used is a qualitative field research method, so that appropriate data results are obtained. So, this research is based on research objects, namely through observation and interviews and through a literature study approach, by collecting data from various sources such as journal articles, books and related documents. The results of the research show that the implementation of religious moderation has a significant impact in increasing harmony between religious people. Through an inclusive and tolerant approach, religious moderation is able to reduce conflict and increase understanding and respect for religious differences. In the context of globalization and increasingly complex religious diversity, the implementation of religious moderation is an important key in building harmony between religious communities. In an effort to achieve this goal, there needs to be cooperation between the government, religious institutions and society as a whole. In conclusion, religious moderation has an important role in promoting harmony between religious communities. Abstrak Jurnal ini membahas tentang implementasi moderasi beragama dan relevansinya terhadap kerukunan beragama pada masyarakat Raren. Tujuan dari penelitian ini adalah untuk mengidentifikasi dan menganalisis peran moderasi beragama dalam mempromosikan kerukunan antar umat beragama di masyarakat.Metode penelitian yang digunakan adalah metode penelitian kualitatif yang berjenis lapangan, sehingga didapatkan hasil data yang sesuai. Jadi, penelitian ini berdasarkan pada objek penelitian yaitu melalui observasi dan wawancara dan melaui pendekatan studi literatur, dengan mengumpulkan data dari berbagai sumber seperti artikel jurnal, buku, dan dokumen terkait.Hasil penelitian menunjukkan bahwa implementasi moderasi beragama memiliki dampak yang signifikan dalam meningkatkan kerukunan antar umat beragama. Melalui pendekatan yang inklusif dan toleran, moderasi beragama mampu mengurangi konflik dan meningkatkan pemahaman serta penghargaan terhadap perbedaan agama.Dalam konteks globalisasi dan keragaman agama yang semakin kompleks, implementasi moderasi beragama menjadi kunci penting dalam membangun kerukunan antar umat beragama. Dalam upaya mencapai tujuan ini, perlu adanya kerjasama antara pemerintah, lembaga agama, dan masyarakat secara keseluruhan.Kesimpulannya, moderasi beragama memiliki peran yang penting dalam mempromosikan kerukunan antar umat beragama. Kata Kunci: Moderasi, Beragama, Masyarakat.